Changes in fat metabolism in the seasonal body mass cycle of captive Svalbard rock ptarmigan (Lagopus muta hyperborea) - Aspelund, Linn (UiT Norges arktiske universitet, 2021)
The Svalbard ptarmigan exhibits profound seasonal variations in body mass. The deposition of fat in the fall is an adaptation that allows the ptarmigan to survive periods of food shortages during the Arctic winter. In this study, previously unexplored molecular aspects of this well- established body mass cycle were investigated. Captive Svalbard ptarmigan fed ad libitum and kept under short photoperiod were moved to constant light. Birds were sampled at four different stages in the body mass cycle and longitudinal measurements of physiology and behavior were taken throughout the study. In order to assess molecular control of their body mass cycle I measured the expression of six key elements of fat metabolism by qPCR. The expression of these lipid metabolism genes suggested that fatty acid synthesis was downregulated during the weight-loss phase and upregulated during the weight-gain phase, while lipolysis and fatty acid oxidation was downregulated in the weight-gain phase. Gene expression was also correlated to food intake, suggesting increased lipogenesis and decreased lipolysis and oxidation with high food intake. Results from Oil Red O (ORO) staining indicated that heart and muscle tissues of Svalbard ptarmigan are protected from excess accumulation of fat. ORO staining of liver tissue further revealed that the amount of fat in the liver varied during the BM cycle and was highest when the birds were fat during the short photoperiod. The average size of fat cells was higher in fat birds compared to lean birds, suggesting that the change in fat depots is accomplished through changes in fat cell sizes rather than cell numbers.